The Technique for the Development of Basic Preschool Teacher and Parental Competencies - V. B. Veretennikova; O. F. Shikhova; Yu. A. Shikhov (Russian State Vocational Pedagogical University, 2019)
Introduction. In recent years, serious changes in the Russian system of preschool education have been observed. These changes are connected not only with the relevant updating of the educational content and introduction of new teaching forms and methods, but also with the need to improve the parents' psychological and pedagogical culture in the questions of upbringing and education of children. In this regard, it is reasonable to consider the possibilities of social partnership between the family and the preschool educational organisation, the potential of which is currently not fully elicited.The aim of the present article is to present the original technique for the development of basic (core) competencies of preschool educators and parents through social partnership between a family and a pre-school educational organisation.Methodology and research methods. While developing the technique, the basic provisions of competency-based, humanistic, system-based and qualimetric approaches were taken into account, thus allowing the authors to implement the principles of individualisation, cooperation and self-organisation. When identifying and evaluating the level of the development of preschool educators' and parents' basic competencies, the method of group expert assessments was used as the main research toolkit. In order to organise and support the development of basic competencies, the authors used case study method, implying practical tasks, discussions and professional simulation games.Results and scientific novelty. Social partnership is considered as the most productive form of relations between the specialists of pedagogical sphere and parents, who are experts in upbringing and understanding of the child. Voluntary and long-term cooperation, based on trust, recognition of mutual responsibility, common goals and values, provides a wide range of opportunities to increase the psychological and pedagogical competency of parents and contributes to the professional growth of the teaching staff of the preschool educational organisation. The authors designed a "reference" thesaurus, which is a hierarchical set of interrelated competencies, needed by each member of the interaction for the full development of a young child. Taking into account the members' individual educational demands and needs, the stages of social partnership are identified: members of pre-school families - in qualified professional assistance and support; children − in educated parents; teachers - in information on the peculiarities of behaviour of pupils outside the preschool educational organisation. The algorithm of formation of basic competencies of teachers and parents of pre-school children was developed and tested in the course of the experiment.Practical significance. The proposed technique can be used for developing social partnership in other pre-school educational organisations, as well as in the system of advanced training for pre-school teachers and in the preparation for their certification as a guidance material, demonstrating the ways of solving the problems, specified in the Federal State Educational Standard of preschool education.